LATE ANTENATAL CARE BOOKING AND ASSOCIATED FACTORS AMONG PREGNANT WOMEN ATTENDING ANTENATAL CARE AT LIRA REGIONAL REFERRAL HOSPITAL, LIRA CITY: CROSS-SECTIONAL STUDY. - Lubwama, James; Francis, Olwa (SJ Insights, 2025)
Background Globally, many pregnant women especially in Sub-Saharan Africa still initiate Antenatal care (ANC) contacts after the first 12 weeks of pregnancy, and yet it is highly associated with increased risk for poor pregnancy outcomes such as preterm delivery, and low birth weight. Therefore, determining the associated factors was crucial to developing the appropriate interventions to combat the problem of late ANC booking with its related complications. Methods This was a cross-sectional study using a quantitative approach to assess the late ANC booking and associated factors among 262 pregnant women attending ANC at Lira Regional Referral Hospital (LRRH) between October 2023 and June 2024. Data was collected using semi-structured questionnaires, coded, and entered into Epi data version 3.1 and exported to SPSS version 23 for analysis. Bivariate and multivariate logistic regression models were utilized to determine factors associated with the outcome variable. Results The prevalence of late ANC booking was 59.5% among pregnant women attending ANC at Lira Regional Referral Hospital, Lira City. Factors that were found significantly associated with late ANC booking at a P-value < 0.02 included; Knowing the ANC frequency [ (AOR)= 0.092; p=0.002; 95%CI; 0.030-0.289], timing of the first ANC [AOR= 68.070; p<0.001; 95%CI; 15.972-290.104], waiting at the facility [AOR=0.326; p=0.013; 95%CI; 0.135-0.786], being uncomfortable telling others that one was pregnant [AOR= 7.308; p= 0.016; 95%CI= 1.455- 36.696] and having a complication in the past pregnancy [AOR= 8.979; p<0.001; 95%CI; 2.639-30.557]. Conclusion The findings in this study indicated that late ANC booking amongst pregnant women attending ANC in the study area was still high. Recommendation Therefore, intervention efforts to improve early ANC booking require targeting of these hindering factors. This can be done by paying special attention to reducing the waiting time at the facility and educating the mothers on the recommended ANC booking time.